How Hedonic Shopping Motivation and Trust Shape Purchasing Decisions Among Shopee PayLater Users ? - Nudiya Nudiya; Suwarto Suwarto; Andry Stepahnie Titing (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study explores the impact of hedonic shopping motivation and trust on purchasing decisions among Shopee PayLater users in Kolaka Regency. Using a quantitative approach with Structural Equation Modeling (SEM) and Partial Least Squares (PLS), data were gathered from respondents through both hard-copy and online questionnaires. The findings reveal that both hedonic shopping motivation and trust significantly influence purchasing decisions, with trust playing a more dominant role. Consumers who shop for emotional gratification, excitement, and impulse buying tendencies are more likely to make purchases using Shopee PayLater. Additionally, trust in the platform’s reliability, transparency, and security strongly affects consumer decisions, reinforcing the importance of credibility in digital transactions. While these two factors explain a substantial portion of purchasing behavior, other external variables such as price, product quality, promotions, and financial literacy also contribute. These results provide valuable insights for e-commerce platforms, financial institutions, and policymakers in optimizing digital payment systems and promoting responsible consumer spending. Future research should incorporate additional factors to develop a more comprehensive understanding of consumer decision-making in buy-now-pay-later (BNPL) services and e-commerce environments.